Muhammadiyah Studies: The Transformation of Research on Islamic Movement in Indonesia - Mutohharun Jinan (Analisa: Journal of Social Science and Religion, 2015)
This research aims to describe the studies of the Muhammadiyah movement. Scholars have condukted research, observations, and discussions of the Movement. This research is not limited the Muhammadiyah as an Islamic movement, but also its role as economic,educational, and socio-political movement. Research and discussion on the various dimensions of Muhammadiyah are called "Muhammadiyah Studies". By hitoriographical approach, there are three stages of development in the Muhammadiyah Studies. First, study of the fundamental of islamic teaching (1912-1950). Sceond, the preriod wich the Muhammadiyah Studies as a part of modern islamic studies (1950-200). Thrid, after 200s, Muhammadiyah Studies is Characterized by new themes as a part of papular culture.